Analysis of the effects of wind barrier on driving safety and comfort of vehicles on long-span bridges under crosswinds. (August 2022) - Zou, Yunfeng; Xue, Fanrong; Shi, Kang; He, Xuhui; Han, Yan; Liu, Qingkuan; Li, Lianfang
Abstract: The installation of wind barriers is generally considered able to improve traffic safety on bridges. Conventionally, the effects of wind barriers are evaluated through the aerodynamic characteristics or dynamic responses of vehicles. In this study, the effects of wind barriers are numerically investigated from the driving safety and comfort perspectives for the first time. The methodology for dynamic analysis of wind–vehicle–bridge (WVB) coupled system is firstly present. Then, the evaluation indexes for driving safety and comfort of vehicles are proposed. A series of wind-tunnel experiments are conducted, and corresponding numerical calculations are performed to discuss the influence of wind barrier parameters i.e., height and opening ratio. Through dynamic responses derived from the calculation results, it is confirmed that: (1) the lateral dynamic responses for both vehicles and bridges considerably increase under winds excitation; (2) the installation of wind barriers can effectively prevent traffic accidents on a bridge, and is thus an effective windproofing measure; (3) however, this method is not beneficial to the bridge structure in terms of stresses and significantly increases the overall vibration value total value (OVTV) of vehicles, which is not conducive to the driving comfort of vehicles on the bridge.